The Potential Roles of Ghrelin in Metabolic Syndrome and Secondary Symptoms of Alzheimer’s Disease - Kim, Sujin; Nam, Yunkwon; Shin, Soo Jung; Park, Yong Ho; Jeon, Seong Gak; Kim, Jin-il; Kim, Min-Jeong; Moon, Minho (Frontiers in Neuroscience, 2020)
Although the major causative factors of Alzheimer’s disease (AD) are the accumulation of amyloid beta and hyperphosphorylated tau, AD can also be caused by metabolic dysfunction. The major clinical symptom of AD is cognitive dysfunction. However, AD is also accompanied by various secondary symptoms such as depression, sleep-wake disturbances, and abnormal eating behaviors. Interestingly, the orexigenic hormone ghrelin has been suggested to be associated with AD-related metabolic syndrome and secondary symptoms. Ghrelin improves lipid distribution and alters insulin sensitivity, effects which are hypothesized to delay the progression of AD. Furthermore, ghrelin can relieve depression by altering the secretion of hormones such as serotonin, noradrenaline, and orexin. Moreover, ghrelin can change the expression of neurotrophic factors such as brain-derived neurotrophic factor and modulate the release of pro-inflammatory cytokines such as tumor necrosis factor-alpha and interleukin-1β. Ghrelin alleviates sleep-wake disturbances by altering the levels of melatonin, melanin-concentrating hormone, γ-aminobutyric acid (GABA), and orexin. Ghrelin reduces the risk of abnormal eating behaviors by altering neuropeptide Y and gamma-Aminobutyric acid. In addition, ghrelin increases food intake by inhibiting fatty acid biosynthesis. However, very few studies have investigated the effects of ghrelin on metabolic disorders and secondary symptoms of AD, so further evidence is required.